Wind energy-harvesting technologies and recent research progresses in wind farm control models - Desalegn, Belachew; Gebeyehu, Desta; Tamrat, Bimrew; Tadiwose, Tassew (Frontiers in Energy Research, 2023)
In order to sustain the overall competitiveness of wind power industry, unrelenting focuses are required on working towards the advancements of enabling technologies, and research studies that are associated with wind farm sys-tems. First, the wind farm technologies that include various turbine generator systems coupled with different power transmission configurations have enormous impacts in determining the qualities of wind power production. In addi-tion, modern wind farms are expected to implement robust power control algorithms to meet more advanced re-quirements of electricity generation. Accordingly, this paper explores the statuses of wind energy harvesting tech-nologies, and wind farm control strategies by discussing on their recent and future impacts in transforming wind power industry. The DFIG-based wind energy harvesting technology is well-matured and has proven to exhibit ex-cellent track-record in past and recent experiences, but its capability of being further scalable for large-scale power production is limited as it is largely incompatible with high voltage power transmission networks. On the other hand, the PMSG-based technology is progressing through significant advancements to attain the maximum possible effi-ciency level in facilitating greatly larger scale power-generation, the construction of bulky and costly power trans-mission systems can be required though. In this regard, future technological advances in wind farm industry are expected to reasonably optimize the design and cost of high voltage power transmission systems. Similarly, increas-ing research studies are mainly introducing a number of power optimization-based control models in aiming to cre-ate ideal integration of the aforementioned wind farm technologies so as to ultimately enhance the reliability of electricity production by maintaining the systems’ safety. Yet, additional works are still expected to be undertaken in the future for more extended evaluation of the performances of different control models under similar environment.